Evaluation of lead in water, soil and its correlation with blood lead levels of the inhabitants of the town of Huacho - Ancash, Peru - 2021 - Avalos-Ramírez, Yosef J. (2023)
The impact of mining activity does not only generate royalties to the government but also contamination by heavy metals such as lead which is one of the main products that cause concern for public health, as they can cause various abnormalities such as headache, irritability, ataxia, seizures, cerebral edema, anemia, renal, hepatic and reproductive failure. In 2018, inhabitants from Huacho (Ancash Region, Perú) complained about lead poisoning. The objective of this research is to determine lead concentrations in soil and water and their correlation with the presence of this metal in the blood of Huacho inhabitants. This research studied the blood results from the 63 tested inhabitants since 71,4% of them had high concentrations of lead in their blood. Samples from drinking and crop irrigation water, and agricultural soil were taken, was analyzed by inductively coupled plasma optical emission spectrometry (ICP-OES. As a result, the analyzed drinking water has 0,029 mg/L, exceeding the limit of 0,01 mg/L indicated by Peruvian legislation. Also, this hat all soil samples contain lead from 12,8 mg/kg to 106,5 mg/kg, which exceeds the maximum limit of 70 mg/kg. In conclusion, the lead occurrence in soil and water correlates with the blood lead levels of Huacho in habitants.